2020
DOI: 10.1097/eja.0000000000001382
|View full text |Cite|
|
Sign up to set email alerts
|

Dexmedetomidine for prevention of postoperative delirium in older adults undergoing oesophagectomy with total intravenous anaesthesia

Abstract: BACKGROUND Dexmedetomidine is known to be a sedative. Recent studies suggest that administration of dexmedetomidine can prevent postoperative delirium (POD) which has been confirmed as a common complication after major surgery. However, its effects in patients undergoing oesophagectomy are scarce. OBJECTIVE To investigate the efficacy and safety of dexmedetomidine in reducing POD in elderly patients after transthoracic oesophagectomy with total intraven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 45 publications
1
55
0
Order By: Relevance
“…Thus, it might have beneficial effects via this mechanism in reducing neuroinflammation. In support of this hypothesis, Hu et al [ 113 ] reported that the surgery-induced increase in IL-6 levels was lower in the patients receiving total intravenous anesthesia (TIVA) with dexmedetomidine compared with those having TIVA without dexmedetomidine.…”
Section: How To Improve Sleep Pre- and Postoperativelymentioning
confidence: 96%
See 1 more Smart Citation
“…Thus, it might have beneficial effects via this mechanism in reducing neuroinflammation. In support of this hypothesis, Hu et al [ 113 ] reported that the surgery-induced increase in IL-6 levels was lower in the patients receiving total intravenous anesthesia (TIVA) with dexmedetomidine compared with those having TIVA without dexmedetomidine.…”
Section: How To Improve Sleep Pre- and Postoperativelymentioning
confidence: 96%
“…It has been shown to prevent POD by reducing the requirement of opioids. Recently, it was also shown to prevent POD in the elderly who were anesthetized with total intravenous anesthesia [ 113 ]. In addition, low-dose (0.1 mg/kg/h) dexmedetomidine improved subjective sleep quality and increased total sleep time and stage N2 sleep in elderly patients in the postoperative ICU [ 114 ].…”
Section: How To Improve Sleep Pre- and Postoperativelymentioning
confidence: 99%
“…DEX is a new type of α2-adrenergic receptor agonist that can simultaneously act on the central and peripheral nervous systems, regulate autonomic nervous activity, and produce dose-dependent sedative, hypnotic and anti-anxiety effects. At the same time, DEX can reduce the incidence of delirium in patients , and it was widely used in the sedative treatment of critically ill patients [26,[32][33][34]. Our study found that, compared to MID, DEX had no signi cant effect on blood pressure at the depth of shallow sedation, At the same time, DEX can also shorten the length of ICU stay.…”
Section: Discussionmentioning
confidence: 60%
“…The overall risk of bias for our primary outcome was low for 10 (30%) studies, 42,45,46,51,58,62,63,66,67,72 and the rest were considered to have some concerns. All studies had satisfactory discussion or documentation regarding missing outcome data.…”
Section: Resultsmentioning
confidence: 96%